1984
DOI: 10.1111/j.1365-2125.1984.tb05027.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic effects of metoprolol and methyldopa on calf blood flow in intermittent claudication.

Abstract: In a placebo-controlled double-blind study 14 hypertensive patients with intermittent claudication were treated with metoprolol (100-200 mg daily) and methyldopa (500-1000 mg daily) for 3 weeks and their effects on heart rate, blood pressure as well as on resting and hyperaemic calf blood flow and vascular resistance were compared.In their antihypertensive effect metoprolol and methyldopa did not differ significantly. In 23 diseased limbs the calf blood flow and vascular resistance remained unchanged at rest d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…Some studies showed worsening of intermittent claudication in response to therapy with ␤-receptor blockers, but the number of patients included into these trials was quite small. [13][14][15][16][17] Based on these findings, a recent meta-analysis concluded that, because of lack of large randomized trials, ␤-blockers should be used with caution in patients with intermittent claudication. 22 Nevertheless, despite possible adverse effects on clinical symptoms, ␤-blockers are widely used in PAD patients because of their prognostic impact, clinical experience suggests that ␤-blockers are often well tolerated in daily practice, and current guidelines recommend their use in PAD patients if indicated in particular in patients with CAD and arterial hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies showed worsening of intermittent claudication in response to therapy with ␤-receptor blockers, but the number of patients included into these trials was quite small. [13][14][15][16][17] Based on these findings, a recent meta-analysis concluded that, because of lack of large randomized trials, ␤-blockers should be used with caution in patients with intermittent claudication. 22 Nevertheless, despite possible adverse effects on clinical symptoms, ␤-blockers are widely used in PAD patients because of their prognostic impact, clinical experience suggests that ␤-blockers are often well tolerated in daily practice, and current guidelines recommend their use in PAD patients if indicated in particular in patients with CAD and arterial hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…6 -12 On the one hand, ␤-blockers are contraindicated in the setting of severe PAD, and previous studies reported a worsening in parameters related to quality of life, functional capacity, and clinical symptoms also in stable PAD patients treated with nonvasodilating ␤-blockers. [13][14][15][16][17] On the other hand, some studies did not show adverse effects of ␤-blockers in PAD patients. 18 -21 In addition, several meta-analyses suggest that ␤-blockers do not adversely affect walking distance in patients with intermittent claudication.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the studies included in this review were performed in Finland, 12,13) Denmark, 14,15) Belgium, 16,17) Israel, 18) and the USA. 16,19) Investigation of racial diŠerences and a-receptor sensitivity in patients with IC is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore appropriate to assess the effects different antihypertensive agents may have on limb blood flow and vascular resistance during treatment. Further, such measurements may be useful in predicting the effects of antihypertensive agents on the lower limb circulation in patients with hypertension complicated by peripheral vascular disease (McSorley & Warren, 1978;Lepantalo, 1984). Changes in limb blood flow may be a direct consequence of alteration in vascular resistance, a change in cardiac output (C.O.)…”
mentioning
confidence: 99%